Strategi Direktorat Jenderal bea dan Cukai (DJBC) Dalam Manajemen Komunikasi Krisis - Deanna Amanda Putri; Andre Noevi Rahmanto (Jurnal Komunikasi Massa, 2024)
In the digital era, public perception of an organization or institution can be easily shaped and rapidly changed. This is due to the ease of access to information and its dissemination through social media, online news, and other digital platforms. In this environment, both accurate and inaccurate information can quickly go viral, influencing public opinion within minutes or hours. As a result, an organization's reputation can be significantly impacted, either positively or negatively, depending on how the information is interpreted by the public. Direktorat Jenderal Bea Dan Cukai (DJBC) faced crisis communication issues due to several incidents that occurred in April-May 2024, involving;1). imported shoes, 2). donated equipment for Sekolah Luar Biasa (SLB), and 3). robotic shipments. These crises have triggered negative sentiment from the public toward DJBC. This study uses a qualitative approach with a case study method and purposive sampling technique to collect data through interviews with six (6) informants. Based on the Situational Crisis Communication Theory (SCCT), DJBC has navigated the pre-crisis, crisis, and post-crisis phases by implementing communication strategies that include a deny strategy with denial and scapegoat elements, diminish strategy through excuses during the crisis, and rebuild strategy through apology and bolstering strategy via reminders and ingratiation in the post-crisis phase. An analysis of the three main factors determining the threat of a crisis to an organization Crisis Responsibility, Crisis History, and Prior Relational Reputation indicates that DJBC faces significant challenges in managing its crisis communication in the current era.